To Investigation of Plastic Concrete Bentonite Changes on it's Physical Properties - Kazemian, Sina; Ghareh, S.; Torkanloo, L. (ELSEVIER SCIENCE BV, 2016)
Bentonite is one of the most important materials in Plastic concretes due to causes to fill voids of concretes. Plastic concrete is well known as a suitable material for building earth dam cut off due to low permeability, high deformability and enough strength to withstand applied stresses. In this study, we have investigated the effect of the ratio of mixing materials (mixture proportions) and cement as well as the materials' quality such as the type of bentonite on marsh, compressive strength and modulus elasticity of plastic concrete. The results of this study showed that by decreasing the ratio of term activity, compressive strength will be reduced due to increasing free water in case of the stability of other parameters. However, the effect of cement has direct effect on mechanical properties of plastic concrete.